Kinerja Karyawan Ditinjau Dari Gaya Kepemimpinan, Lingkungan Organisasi, Kompensasi Dan Kepuasan Kerja Sebagai Variabel Moderating Studi Empiris Pada Bank Konvensional Dan Bank Syariah Di Surakarta - Setyorini, Dwi; , Dr. Fatchan Ahyani, SE., M.Si (2016)
This research was conducted on convention and sharia banking in Surakarta. The purpose of this research was to analyze the factor that affect the employees performance. The affecting factors was seen through the leadership style, organizational environment, compensation and job satisfaction as moderating variable. The population of this research are the employees in conventional and sharia banking in Surakarta. Total research sample was 45 employees which determind with convenience sampling method. Data analysis was performed with classic assumption test and hypothesis test with multiple regression method. The result of this research indicate the factors that affect the employees performance are leadership style, organizational environment, and compensation have some affects toward employees performance, while job satisfaction did not have any affect toword employees performance, and job satisfaction moderated the relation between leadership style and compensation to employees performance, while job satisfaction did not modarate the relation between organizations environment with employees performance in conventional and sharia banking.